Evaluation of the Role of Type-1 Interferon Signaling in the Pathogenesis of Salmonella Typhimurium - Verma, Priya (Université d'Ottawa / University of Ottawa, 2022)
Innate immunity operates independently of prior exposure to pathogens. There are several signal transduction pathways that play a key role in inflammatory and immune responses. Critical signaling cascade in the interest of my research is type-1 interferon (IFN) signaling pathway in response to infection with Salmonella Typhimurium (ST). The role of type-I interferons is well established in the context of a viral infection; however, their role in bacterial infections is not clear. In my thesis I aimed to understand the role of type-1 IFNs in bacterial pathogenesis, and scrutinize the mechanism adopted by various components of type-1 IFN signaling, especially ISGF3 complex in response to Salmonella Typhimurium. My results indicate that type-I IFN signaling is detrimental to host survival. I further investigated the mechanism through which type-1 IFN signaling results in host susceptibility against Salmonella. My results indicated that the three transcription factors downstream of IFNAR1 have different impacts in mounting an innate immune response against ST. IRF9 and STAT2 promote susceptibility against ST whereas STAT1 through IFNAR1-signaling, promotes enhanced expression of pro inflammatory cytokines and protection against ST. I also observed that the monocytes/macrophages lineage in Ifnar1⁻ᐟ⁻ mice is responsible for conferring the enhanced resistance against ST. Furthermore, my work determined that expression of type-I IFN signaling compromises the fitness of macrophages by reducing mitochondrial respiration, glycolysis and myelopoiesis.
Keywords: Salmonella Typhimurium; Type-1 interferon; Myelopoiesis; Innate Immunity